#TITLE_ALTERNATIVE# - REZA PAMBUDI NIM : 12208064), ALDY
Pressure temperature spinner (PTS) survey is performed in a two phase geothermal well. Quantitative analysis is performed from PTS survey of two phases geothermal well to get feedzone parameters like depth of the feedzone, mass rate, and fluid enthalpy. Spinner rotation data in revolution per second is used to calculate fluid velocity along the wellbore. Mass rate and fluid enthalpy profiles are calculated using mixed fluid density predicted using derivation of homogeneous pressure loss equation. A wellbore flow simulation using homogenous model is developed to predict multi-feedzone flow in well. This wellbore flow simulation is calibrated using pressure, temperature, fluid velocity, mass rate, and fluid enthalpy data from PTS survey. Calibration is performed by inputing feedzone parameters such as location, mass rate contribution, and fluid enthalpy of a feedzone until the simulation result matched with the observed data. Feedzone parameters predicted using developed homogeneous wellbore simulation give a consistence result with observed data from PTS survey of two phases geothermal well in water-dominated steam-caped reservoir. By using this simple analysis method, the existence of steam cap could be confirmed better.